2019
DOI: 10.1259/bjr.20190530
|View full text |Cite
|
Sign up to set email alerts
|

Iodine quantification and detectability thresholds among major dual-energy CT platforms

Abstract: Objectives: To estimate the minimum detectable iodine concentration on multiple dual-energy CT (DECT) platforms. Methods and materials: A phantom containing iodine concentrations ranging from 0 to 10 mg ml−1 was scanned with five dual-energy platforms (two rapid kilo volt switching (r-kVs), one dual source (DS), one sequential acquisition and one split-filter). Serial dilutions of 300 mg ml−1 iodinated contrast material were used to generate concentrations below 2 mg ml−1. Iodine density and virtual monoenerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Dual-energy CT uses data from two different X-ray spectra, typically with low energy of 80 kVp and high energy of 140–150 kVp ( 18 ). Various types of images can be obtained through data processing using dual-energy CT, such as mixed energy images, iodine maps, virtual non-contrast images, and monoenergetic images ( 12 , 13 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dual-energy CT uses data from two different X-ray spectra, typically with low energy of 80 kVp and high energy of 140–150 kVp ( 18 ). Various types of images can be obtained through data processing using dual-energy CT, such as mixed energy images, iodine maps, virtual non-contrast images, and monoenergetic images ( 12 , 13 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing iodine sensitivity among DECT scanners concluded that it correlates mainly with better spectral performance and is also influenced by other factors such as image reconstruction techniques, patient size, and lesion location [ 34 , 47 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…This prospective, single-center study was approved by the IRB of our university hospital (ClinicalTrials.gov number NCT03146117). We enrolled patients with suspected or confirmed NSCLC, who were referred to undergo a clinically indicated 18 F-FDG-PET/CT staging examination between May 2017 and June 2018, whose age was between 18 and 90 years at the time of the baseline examination, and who provided written informed consent before undergoing any study-related procedures. We excluded patients who (1) were pregnant or nursing females, (2) were in an acute unstable condition, (3) reported prior reactions against iodinated contrast agents, (4) had impaired renal function (glomerular filtration ratio < 30 mL/min × 1.73 m 2 ).…”
Section: Patient Selection and Study Designmentioning
confidence: 99%
“…[14][15][16][17] The material decomposition algorithm for DECT data sets facilitates a precise separation of iodine from other elements and enables the quantification of iodine in a single voxel. 18 Iodine quantification was studied for applications in malignancies diagnosis and prognosis. 14,[19][20][21][22] The integration of a PET/CT and DECT in a single scanner could improve lung cancer staging and provide additional information on tumor pathophysiology.…”
mentioning
confidence: 99%